Learning and Developing Individual Exercise Skills (L.A.D.I.E.S.) for a Better Life: a physical activity intervention for black women - Whitt-Glover, Melicia C. (2012)
Physical activity (PA) is low among African American women despite awareness of its positive impact on health. Learning and Developing Individual Exercise Skills for a Better Life (L.A.D.I.E.S.) compares three strategies for increasing PA among African American women using a cluster randomized, controlled trial. Underactive adult women from 30 churches (n=15 participants/church) were recruited. Churches were randomized to a faith-based intervention, a non-faith based intervention, or an information only control group. Intervention groups will meet 25 times in group sessions with other women from their church over a 10-month period. Control group participants will receive standard educational material promoting PA. All participants will be followed for an additional 12 months to assess PA maintenance. Data will be collected at baseline, 10, and 22 months. The primary outcome is PA (steps/day, daily moderate-to-vigorous PA). We expect treatment effects indicating that assignment to either of the active interventions is associated with greater magnitude of change in PA compared to the control group. In exploratory analyses, we will test whether changes in the faith-based intervention group are greater than changes in the non-faith-based intervention group. L.A.D.I.E.S. focuses on a significant issue—increasing PA levels—in a segment of the population most in need of successful strategies for improving health. If successful, L.A.D.I.E.S. will advance the field by providing an approach that is successful for initiating and sustaining change in physical activity, which has been shown to be a primary risk factor for a variety of health outcomes, using churches as the point of delivery.